Graphical representation of structural data in the field: A methodological proposal for application in deformed areas - Julián Andrés López Isaza; Mario Andrés Cuéllar Cárdenas; Lina María Cetina Tarazona; Anny Julieth Forero Ortega; Ana Milena Suárez Arias; Oscar Freddy Muñoz Rodríguez; Luis Miguel Aguirre Hoyos; María Juliana Gutiérrez López (Boletín Geológico, 2021)
The description of the fabric elements represented by the linear and planar structures present at different scales is a key component of fieldwork. A scheme is proposed for the systematic registration of planes and lineations, coded as S (planar surfaces), F (folds), and L (lineations), among others, that allows for the orderly storage of the measurements taken. This scheme includes information related to the kinematics, the kinematic indicators, and the certainty or reliability ascribed to the assigned movement. In the fieldwork, the graphic representation of the structural measures in modified projection nets includes concentric circles for each dip. Direct drawing of the outcrop data is undertaken, dispensing with the use of tracing or transparent paper. The stereograms resulting from the graphic representation in the modified Wulff stereographic projection net, and the modified Schmidt equal-area net, can be complemented by rose diagrams for visualization of the spatial ordering. During field campaigns in the outcrops, it is essential to visualize the spatial orientation of the data in the diagrams to determine the main structural trends, the vergence, the kinematic nature of faults and shear zones, paleo-stress tensors, and to differentiate structural domains, among others. This information supports the reconstruction of geological and tectonic history and the establishment of relationships between the different geological processes.